2016
DOI: 10.1016/j.jtcvs.2015.08.078
|View full text |Cite
|
Sign up to set email alerts
|

Mitral valve gradient after valve repair of degenerative regurgitation with restrictive annuloplasty

Abstract: Mitral valve repair for degenerative regurgitation results in a small mitral valve gradient that appears to decrease with time after discharge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 10 publications
1
14
0
Order By: Relevance
“…In this study, the mean postoperative MG of 3.1 mm Hg was comparable with those in previous studies. 14 Moreover, the mean prosthetic size of 29.1, despite being seemingly smaller than those in previous studies, became acceptable after being indexed by the relatively small body surface areas. Our results were consistent with previous studies, in which full ring annuloplasty and smaller prosthetic size were associated with elevated PTMGs.…”
Section: Discussionmentioning
confidence: 70%
“…In this study, the mean postoperative MG of 3.1 mm Hg was comparable with those in previous studies. 14 Moreover, the mean prosthetic size of 29.1, despite being seemingly smaller than those in previous studies, became acceptable after being indexed by the relatively small body surface areas. Our results were consistent with previous studies, in which full ring annuloplasty and smaller prosthetic size were associated with elevated PTMGs.…”
Section: Discussionmentioning
confidence: 70%
“…Although the optimal choice of annuloplasty ring type continues to be debated, the present study suggests that full ring is the optimal choice for anterior prolapse. Several studies have examined the effect of annuloplasty type on repair durability, left ventricular function, and functional mitral stenosis after primary mitral repair, 23 but the structure of the prosthesis applied has not been extensively discussed. Spiegelstein and colleagues 6 reported that the use of open annuloplasty rings is an independent predictor of late recurrence of moderate or severe mitral regurgitation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that, compared to partial rings, complete rings may be associated with higher MV gradients 16 . Another report also supports the concept that restrictive annuloplasty results in small valve gradients 15 . However, in our cohort, only the iTEE MPG values were higher in the total annuloplasty group, and only the post-TTE MPG values were higher in the partial annuloplasty group.…”
Section: Discussionmentioning
confidence: 54%